(untitled) (gjstudies, 2019)
This research investigates the longitudinal efficacy of a novel, narrative-based pedagogical framework for accounting ethics training, contrasting it with traditional rule-based and case-study methods. While existing literature extensively documents the necessity of ethics education, it predominantly focuses on short-term knowledge acquisition and declarative understanding of professionalcodes. This study introduces and evaluates the ’Ethical Scenario Immersion and Reflection’ (ESIR)model, a methodology grounded in cognitive narrative theory and immersive simulation, designedto foster deeper ethical reasoning schemata and prosocial behavioral intentions. We posit that byengaging accounting students and early-career professionals in extended, morally ambiguous narrative scenarios requiring iterative decision-making with simulated consequences, the ESIR modelcan more effectively bridge the gap between abstract ethical principles and concrete professionalconduct than conventional approaches. A mixed-methods, quasi-experimental design was employedover a 24-month period with a cohort of 312 participants from undergraduate accounting programsand public accounting firms. Quantitative measures assessed changes in ethical sensitivity, reasoning complexity (using a modified Defining Issues Test), and behavioral intent across three training modalities: ESIR, traditional case-based, and a control rule-review module. Qualitative data,gathered through post-intervention reflective journals and follow-up interviews, provided nuancedinsights into the cognitive and affective processes engendered by the training. Results indicate thatparticipants in the ESIR cohort demonstrated a statistically significant and sustained increase inethical reasoning complexity and a greater propensity to identify nuanced ethical issues in complex,multi-stakeholder scenarios, compared to other groups. Notably, the ESIR group’s reflective journalsexhibited a marked shift from deontological, rule-centric reasoning toward more consequentialistand virtue-based frameworks, suggesting a diversification of ethical schemata. Furthermore, sixmonth follow-up data from early-career professionals suggested a correlation between ESIR training and self-reported confidence in navigating real-world ethical dilemmas, though causal claimsare tempered by contextual variables. This research contributes originality by applying narrativecognition frameworks to accounting ethics pedagogy, proposing a measurable shift from teachingethics as a static body of knowledge to cultivating it as a dynamic, situated practice. The findingschallenge the sufficiency of code-centric training and advocate for pedagogical models that simulatethe phenomenological complexity of ethical decision-making in accounting practice.